2022
DOI: 10.21037/jgo-22-545
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenectomy with venation is preferred compared to skeletonization for patients with rectal and sigmoid colon cancer: a retrospective cohort study

Abstract: Background: For patients with rectal and sigmoid colon cancer, dissecting No. 253 lymph nodes and preserving the left colic artery are the essentials of radical surgery. In clinical work, some surgeons prefer to dissect lymph nodes with skeletonization, believing that lymph nodes can be dissected completely by this method, while other surgeons prefer to dissect lymph nodes with venation. They believe that their method can not only dissect lymph nodes completely but also ensure the safety of patients. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Surgical treatment is an effective therapy for rectal tumors. It is reported that lymphadenectomy with venation is preferred for radical resection in some patients ( 53 ). Rectal cancer patients have more symptoms and decreased performance status in the presence of advanced disease, and the quality of life of these patients can also be impacted ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is an effective therapy for rectal tumors. It is reported that lymphadenectomy with venation is preferred for radical resection in some patients ( 53 ). Rectal cancer patients have more symptoms and decreased performance status in the presence of advanced disease, and the quality of life of these patients can also be impacted ( 54 ).…”
Section: Discussionmentioning
confidence: 99%